Safety and efficacy of spider anchoring device for apical repair in laparoscopic sacrocolpopexy: Retrospective cohort study. (April 2019) - Braun, Naama Marcus; Andraos, Wael; Bettin, Stefan
Abstract: Objective: The aim of the study was to assess safety and efficacy of apical support when using the soft-tissue metal fasteners of EndoFast Reliant™ SCP during laparoscopic sacrocolpopexy (LSCP). Study design: This is a single-center, retrospective cohort study including all patients which underwent LSCP between 2015 and 2017. Safety outcome included the procedure and the device related complications. Effectiveness outcomes included the anatomical success of apical repair and the functional results as were obtained from the clinic and from a Quality of life questionnaire (PFDI-20). Results: Eighty-four patients, 54% with grade III and IV prolapse were included in the study. Uterus was preserved in 68% of patients with uterus. Mean follow-up period for the clinic visit was 4.5 ± 4 months. Short term anatomical success was achieved for 98.8% of the patients. Marked improvement was observed in the related symptoms including urinary incontinence. Three intra-operative complications occurred: 1 case of bladder injury, 1 case of intra-abdominal bleeding, and 1 case of post-operative vaginal bleeding. Later complications included only two patients (2.3%) complained of chronic abdominal pain. There were no cases of mesh erosion or de-novo dyspareunia. The mean follow-up period for the PFDI-20 questionnaire was 15.6 months. 75% of patients had no bulge symptoms at all. Quarter of the patients had some bulge symptoms, bothers them between somewhat to moderately according to the questionnaire grading. Conclusions: The use of Endofast SCP fasteners for laparoscopic promonto-fixation is a safe and effective surgery. Longer follow-up and larger studies should be performed to establish the results.